(untitled) (Fiep Bulletin - online, 2013)
The present study aims to contribute to improving the quality of life of employees of the Municipal School of Basic Education José Francisco de Andrade Santana do Ipanema, Alagoas, through the deployment of Gymnastics Program.Teachers living in their school, vigilant, general services and staff.A questionnaire will be Anamnesis, in order to know the habits of the participants. The socioeconomic status will be analyzed through the ABEP / ABIPEME (OROZCO, 1999 - ANNEX A) Test Lipp (LIPP, 2000 - APPENDIX B) to analyze symptoms of stress, and the Test - Checklist for Diagnosis of Disease Hurry the (Seiwert, 2004 - APPENDIX C). Employees participated in Gymnastics Compensatory three times a week for 10 minutes in the middle of the workday, being developed stretching exercises, motor coordination and strength and circle dances.The comparison of the data obtained each week seeking to know what is the best way to apply breaks with exercise - Gymnastics. In interpreting the data - Evaluation Personnel and Labor, must be observed.